Diversification in Feeding Pattern of Livestock in Early Bronze Age Northwestern China - Qiu, Menghan; Li, Haoran; Lu, Minxia; Yang, Yishi; Zhang, Shanjia; Li, Ruo; Chen, Guoke; Ren, Lele (Frontiers in Ecology and Evolution, 2022)
Animal husbandry has been an indispensable part of human subsistence since the origin of agriculture. Along with the prehistoric cultural exchange, several kinds of major domestic animals diffused and gradually gotten popularized across the Eurasia. The specific geographic setting makes the Hexi Corridor in northwestern China one of the key regions to converge various types of major crops and livestock, and to witness the deep impact of novel species on local subsistence. Archaeological evidence reveals an emergence of early oriental-occidental cultural communication at the opening of the local Bronze Age in Hexi Corridor, resulting in a significant shift of local subsistence. However, due to the lack of more detailed archaeological evidence, the initial timing and trajectory of the transformation of livestock feeding patterns remain unclear. Here we report systematic stable isotope and precise radiocarbon dating analyses on faunal remains unearthed from Huoshiliang and Ganggangwa, two Early Bronze Age settlements (ca. 4000–3700 BP) in middle Hexi Corridor. Our results show distinct diversification in livestock feeding patterns at 3850 cal BP; in contrast with previous periods, some omnivorous livestock appear to have consumed mainly C3 foodstuff and some herbivorous livestock primarily consumed C4 plants. Combined with published stable isotope data and other archaeological findings in the neighbouring region, a clearer trajectory of the evolution of livestock feeding patterns has been revealed with diversified strategy amid the transformation during the Early Bronze Age in Hexi Corridor. We argue that the alteration of the local livestock feeding pattern reflects the attempt to achieve more efficient economy and sustainable society, to withstand the harsh arid environment in Hexi Corridor.